Demonstration of elevated levels of active cathepsin S in dextran sulfate sodium colitis using a new activatable probe. Issue 11 (24th August 2015) - Barlow, N.; Nasser, Y.; Zhao, P.; Sharma, N.; Guerrero‐Alba, R.; Edgington‐Mitchell, L. E.; Lieu, T.; Veldhuis, N. A.; Poole, D. P.; Conner, J. W.; Lindström, E.; Craig, A. W.; et al.
Abstract Background Proteases play a major role in inflammatory diseases of the gastrointestinal tract. Activatable probes are a major technological advance, enabling sensitive detection of active proteases in tissue samples. Our aim was to synthesize an activatable probe for cathepsin S and validate its use in a mouse model of colitis. Methods We designed and synthesized a new fluorescent activatable probe, NB200, for the detection of active cathepsin S. Colitis was induced in C57BL/6 mice by the administration of 3% dextran sulfate sodium (DSS). Homogenized mouse colons, with or without the addition of the specific cathepsin S inhibitor MV026031, were incubated with NB200 in a fluorescent plate reader. Key Results NB200 selectively detected purified cathepsin S and not other common inflammatory proteases. Homogenates of colon from mice with DSS colitis induced a significant fluorescent increase when compared to control animals (control vs DSS: p < 0.05 at 200 min and p < 0.01 at 220–240 min), indicating cathepsin S activation. The cathepsin S inhibitor abolished this increase in fluorescence (DSS vs DSS + MV026031: p < 0.05 at 140 min, p < 0.01 at 180 min, p < 0.001 at 200–240 min), which confirms cathepsin S activation. Cathepsin S activity correlated with the disease activity index (Spearman r = 0.77, p = 0.017). Conclusions & Inferences Our investigation has demonstrated the utility of activatable probes for detecting protease activity in intestinal inflammation. Panels of such probes may allow 'signature' protease profiles to be established for a range of inflammatory diseases and disorders.